End Group Dye‐Labeled Polycarbonate Block Copolymers for Micellar (Immuno‐)Drug Delivery. Issue 12 (10th April 2022) - Czysch, Christian; Medina‐Montano, Carolina; Dal, Nils‐Jørgen Knudsen; Dinh, Thi; Fröder, Yannick; Winterwerber, Pia; Maxeiner, Konrad; Räder, Hans‐Joachim; Schuppan, Detlef; Schild, Hansjörg; Bros, Matthias; Biersack, Bernhard; et al.
Abstract: Defined conjugation of functional molecules to block copolymer end groups is a powerful strategy to enhance the scope of micellar carriers for drug delivery. In this study, an approach to access well‐defined polycarbonate‐based block copolymers by labeling their end groups with single fluorescent dye molecules is established. Following controlled polymerization conditions, the block copolymers' primary hydroxy end group can be converted into activated pentafluorophenyl ester carbonates and subsequently aminolyzed with fluorescent dyes that are equipped with primary amines. During a solvent‐evaporation process, the resulting end group dye‐labeled block copolymers self‐assemble into narrowly dispersed ∼25 nm‐sized micelles and simultaneously encapsulate hydrophobic (immuno‐)drugs. The covalently attached fluorescent tracer can be used to monitor both uptake into cells and stability under biologically relevant conditions, including incubation with blood plasma or during blood circulation in zebrafish embryos. By encapsulation of the toll‐like receptor 7/8 (TLR7/8) agonist CL075, immune stimulatory polymeric micelles are generated that get internalized by various antigen‐presenting dendritic cells and promote their maturation. Generally, such end group dye‐labeled polycarbonate block copolymers display ideal features to permit targeted delivery of hydrophobic drugs to key immune cells for vaccination and cancer immunotherapy. Abstract : The controlled synthesis of polycarbonate block copolymers is leveraged to generate active ester carbonate end groups that allow defined attachment of fluorescent dyes. Applications as micellar delivery systems for hydrophobic (immuno)‐drugs demonstrate their advantageous properties as long‐circulating particles in the blood stream and for maturating antigen‐presenting immune cells.